Experience of Breast Clinic in a Tertiary Level Hospital - Islam, Sharmin; Rahman, Ayesha; Elahi, Mahboob; Nahar, Mst Jesmen; Sultana, Salma; Tani, Sadia Afrin; Jamal, ABM (Journal of Dhaka Medical College, 2023)
Background: Breast cancer is the second leading cancer worldwide (2089 million new cases per year, 11.6%) after lung cancer and 5th most leading cause of death (6.6%). The breast clinic concept is to set up a center of a cohesive group of dedicated breast cancer specialists working together as a multidisciplinary team with access to all the facilities required to deliver highquality care throughout the breast cancer pathway.2 The guidelines note that these professionals do not necessarily have to be based in one location but do need to be in the same geographical area and able to carry out close multidisciplinary work. To provide uniform management of breast diseases, hospital-based breast cancer screening, and properly manage breast cancer patients, we restarted this breast clinic weekly on Thursday in the Outpatient Department of Surgery in Dhaka Medical College Hospital, 2018. Method and Materials: A 1year observational study was done from 1st August 2018 to 31st July 2019. All female patients having breast problems are included in this study by purposive sampling technique. The total number of patients was 620. A database kept using a registrar book, Microsoft Excel, and documents. Results: Out of 620 patients, 26% presented with mastalgia, 50% with a breast lump, 15% with Fibrocystic changes, 4% with nipple discharge, 2 cases with duct papilloma, 2% duct ectasia, and 4% with others. Among the breast lumps, 42% presented with different stages of Carcinoma Breast, 32.4% with Fibroadenoma, 4% with galactocele, 8% breast abscess, 2% with breast TB, 9% with Chronic breast abscess including Granulomatous mastitis. Conclusions: Females are half of the total population, but attention to their problems is not given to that much extent. Therefore, they often presented their symptoms lately. Though mastalgia is a rare symptom of breast cancer, patients are over-conscious regarding breast pain. In contrast, a painless malignant lump grows in its pattern and advances to the T3-4 stage at the presentation time. So providing comprehensive breast care as well as screening with multidisciplinary experts and equipment is a burning need for every tertiary-level hospital. J Dhaka Med Coll. 2022; 31(1) : 93-97